Low concentrations of Ambrosia maritima L. phenolic extract protect endothelial cells from oxidative cell death induced by H2O2 and sera from Crohn's disease patients. (10th January 2023) - Ramli, Iman; Posadino, Anna Maria; Zerizer, Sakina; Spissu, Ylenia; Barberis, Antonio; Djeghim, Hanane; Azara, Emanuela; Bensouici, Chawki; Kabouche, Zahia; Rebbas, Khellaf; D'hallewin, Guy; Sechi, Leonardo Antonio; et al.
Abstract: Ethnopharmacological relevance: A rising resort to herbal therapies in Crohn's disease (CD) alternative treatments has been recently observed due to their remarkable natural efficiency. In this context, the weed plant Ambrosia maritima L., traditionally known as Hachich el Aouinet in Algeria and as Damsissa in Egypt and Sudan, is widely used in North African folk medicine to treat infections, inflammatory diseases, gastrointestinal and urinary tract disturbances, rheumatic pain, respiratory problems, diabetes, hypertension and cancer. Aim of the study: To assess an Ambrosia maritima L. phenolic extract for its phenolic profile composition, its potential antioxidant activity in vitro, and its cytoprotective effect on cultured primary human endothelial cells (ECs) stressed with H2 O2 and sera from CD patients. Materials and Methods: Phenolic compound extraction was performed with a low-temperature method. Extract chemical profile was attained by HPLC-DAD/ESI-MS. The extract in vitro antioxidant activity was assessed using several methods including cupric ion reducing power, DPPH radical scavenging assay, O-Phenanthroline free radical reducing activity, ABTS cation radical decolourisation assay, Galvinoxyl free radicals scavenging assay. Intracellular reactive oxygen species levels were evaluated in human endothelial cells by H2 DCFDA, while cell viability was assessed by MTT. Results: The phenolic compounds extraction showed a yield of 17.66% with three di-caffeoylquinic acid isomers detected for the first time in Ambrosia maritima L. Using different analytical methods, a significant in vitro antioxidant activity was reported for the Ambrosia maritima L. extract, with an IC50 value of 14.33 ± 3.86 μg/mL for the Galvinoxyl antioxidant activity method . Challenged with ECs the Ambrosia maritima L. extract showed a biphasic dose-dependent effect on H2 O2 -treated cells, cytoprotective and antioxidant at low doses, and cytotoxic and prooxidant at high doses, respectively. Viability and ROS levels data also demonstrated a prooxidant and cytotoxic effect of CD sera on cultured ECs. Interestingly, 10 μg/mL of Ambrosia maritima L. extract was able to counteract both CD sera-induced oxidative stress and ECs death. Conclusion: Our data indicated Ambrosia maritima L. as a source of bioactive phenolics potentially employable as a natural alternative for CD treatment. Graphical abstract: Image 1 Highlights: 3 known phenolic acids were detected for the first time in an Ambrosia Maritima L. extract. The extract shows antioxidant activity in H2 O2 -treated human endothelial cells. The extract shows cytoprotective effect in in H2 O2 -treated human endothelial cells. The extract protects endothelial cells from oxidative damage induced by sera of Crohn's disease patients.